Clinicopathologic and sociodemographic factors associated with late relapse triple negative breast cancer in a multivariable logistic model: A multi-institution cohort study. (February 2023) - Abraham, Adith; Barcenas, Carlos H.; Bleicher, Richard J.; Cohen, Adam L.; Javid, Sara H.; Levine, Ellis G.; Lin, Nancy U.; Moy, Beverly; Niland, Joyce C.; Wolff, Antonio C.; Hassett, Michael J.; Asad, Sarah; et al.
Abstract: Background: Most metastatic recurrences of triple negative breast cancer (TNBC) occur within five years of diagnosis, yet late relapses of TNBC (lrTNBC) do occur. Our objective was to develop a risk prediction model of lrTNBC using readily available clinicopathologic and sociodemographic features. Methods: We included patients diagnosed with stage I–III TNBC between 1998 and 2012 at ten academic cancer centers. lrTNBC was defined as relapse or mortality greater than 5 years from diagnosis. Features associated with lrTNBC were included in a multivariable logistic model using backward elimination with a p < 0.10 criterion, with a final multivariable model applied to training (70%) and independent validation (30%) cohorts. Results: A total 2210 TNBC patients with at least five years follow-up and no relapse before 5 years were included. In final multivariable model, lrTNBC was significantly associated with higher stage at diagnosis (adjusted Odds Ratio [aOR] for stage III vs I, 10.9; 95% Confidence Interval [CI], 7.5–15.9; p < 0.0001) and BMI (aOR for obese vs normal weight, 1.4; 95% CI, 1.0–1.8; p = 0.03). Final model performance was consistent between training (70%) and validation (30%) cohorts. Conclusions: A risk prediction model incorporating stage, BMI, and age at diagnosis offers potential utility for identification of patients at risk of development of lrTNBC and warrants further investigation. Highlights: Triple negative breast cancer (TNBC) late relapse may occur >5 years post-diagnosis. Stage and body mass index were associated late relapse in a multivariable model. We developed a risk prediction model for patients at risk of late relapse. This work supports further investigation factors associated with late relapse TNBC.